CEO Characteristics: Solution to Improving Environmental Disclosure - Ainun Fadila Azzahra; Shinta Permata Sari (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study examines the influence of Chief Executive Officer (CEO) characteristics on the level of environmental disclosure in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The CEO characteristics examined include tenure, gender, age, education, duality, and nationality. Environmental disclosure is measured using the Global Reporting Initiative (GRI) standards. The research method uses quantitative analysis with multiple linear regression to test the effect of independent variables on Environmental Disclosure. This research fills the gaps left by previous studies. This study using purposive sampling, 88 companies-year observations were analyzed through Multiple Linear Regression. The study found that CEO Tenure, CEO Gender, CEO Education, and CEO Nationality does not have an effect on Environmental Disclosure. Conversely, CEO Age and CEO Duality have an effect on Environmental Disclosure. This study aims to provide empirical understanding regarding the role of the CEO in enhancing company transparency and accountability on environmental issues as part of sustainable business strategies. The research results are expected to serve as considerations for companies in selecting and developing CEOs who can promote environmental disclosure, as well as assist the government and stakeholders in designing policies and assessing the performance of sustainable corporate governance.